STATUS KESEHATAN PERIODONTAL DAN TINGKAT KEBUTUHAN PERAWATAN PASIEN YANG DATANG KE KLINIK PERIODONSIA RSGM UNIVERSITAS JEMBER TAHUN 2011 - Ermawati, Tantin; Sari, Desi Sandra; Melok, M (Fakultas Kedokteran Gigi Universitas Jember, 2012)
The CPITN is a screening procedure for identifying actual and potential problems posed by periodontal disease. The aim of this study was to know periodontal status and periodontal treatment needs from patient that come to RSGM department periodontia faculty of dentistry Jember University in the year 2011. The study population comprised 191 adolescences (10 â 59 years). An observational study was conducted at RSGM of Jember University. The results of the study showed that individuals with a health periodontium is 1.05 %, score (1) with bleeding on probing is 3.14 %. Periodontal pocket (4-5mm) was recorded 17.27 %. The highest periodontal score is scores 2 (calculus) 78.53% of the population need dental scaling. We conclude that prevalence periodontal disease in patients that come to periodontics department is very high and periodontal treatment need with scaling.